FUNDAMENTAL BASIS AND APPLICATION OF COLD-ROOM PROJECT DESIGN: A CASE STUDY OF FRIGOSHIP - Ozturk, Merve; Goktepe, Emine; Celen, Ali; Cebi, Alican; Dalkilic, Ahmet Selim; Wongwises, Somchai (AMER SOC MECHANICAL ENGINEERS, 2014)
In this paper, a cold-room system in a frigoship was analyzed as a case study to demonstrate the application of the proposed model. The model was also evaluated in terms of the alteration of alternative refrigerants and insulation thickness of the cold rooms' refrigeration system. The coefficients of performance (COP), refrigerant charge rates, and capacities of each component of the refrigeration system for the refrigerants CFC-12, HCFC-22 and their alternatives, such as HFC-134a, HFC-410a, HFC-404a, HFC-407c, and HFC-507 were determined by considering the effects of the main parameters of the performance analysis, such as refrigerant type, Based on the results of the energy analyses, all of the alternative refrigerants have a slightly lower COP and require higher compressor work than CFC-12 and HCFC-22 for condensation temperature of 40 degrees C. The hunted fishes have an evaporation temperature of 25 degrees C regarding with the preserved product in the case studies. Effects of isolation thickness of wall on evaporator capacity and sea water temperature on condenser are also investigated. Also variation capacity of system components such as evaporator, condenser and compressor with relative humidity of neighbor volume is studied.
Keywords: ADIABATIC CAPILLARY TUBES; HYDROCARBON MIXTURES; FLOW CHARACTERISTICS; REPLACE HFC-134A; REFRIGERANTS; SYSTEM; Thermodynamics; Engineering